2021
DOI: 10.3390/d13110554
|View full text |Cite
|
Sign up to set email alerts
|

Coral Communities on Marginal High-Latitude Reefs in West Australian Marine Parks

Abstract: Many temperate reefs are experiencing a shift towards a greater abundance of tropical species in response to marine heatwaves and long-term ocean warming worldwide. Baseline data for coral communities growing in high-latitude reefs is required to better understand ecosystem changes over time. In this study, we explore spatial and temporal trends in the distribution of coral communities from 1999 to 2019 at 118 reef sites within the five marine parks located in the south-west of Western Australia (WA) between 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 82 publications
(133 reference statements)
0
3
0
Order By: Relevance
“…Substantial poleward range shifts have already occurred for coral species globally (Abrego et al, 2021) and in eastern and western Australia (Baird et al, 2012; Booth & Sear, 2018; Ross et al, 2021). Our projections indicate likely shifts of suitable thermal conditions for coral by several hundred kilometres in south‐eastern Australia by the end of the century.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial poleward range shifts have already occurred for coral species globally (Abrego et al, 2021) and in eastern and western Australia (Baird et al, 2012; Booth & Sear, 2018; Ross et al, 2021). Our projections indicate likely shifts of suitable thermal conditions for coral by several hundred kilometres in south‐eastern Australia by the end of the century.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the strong morphological resemblance between C. monile and C. marshae, both species may appear to be synonymous, but this would not change the finding that C. marshae is not a high-latitude endemic. The present record gives cause to new debate concerning the range of this species, in particular with regard to climate and endemism, which may also be relevant for other high-latitude species in light of the expected tropicalization of high-latitude reefs [14,20,21].…”
Section: Introductionmentioning
confidence: 97%
“…The assessment of climate change refugia status also relies on detailed baseline benthic data and the resilience of coral communities to global change such as rising sea surface temperature (SST). For example, a study by Ross et al, (2021) [5] which provides a detailed 20-year study of 118 high-latitude reef sites in five marine parks located in the South-West of Australia, found that current conditions were favourable to the ongoing survival of existing coral genera. Further, there had been minimal signs of expansion in coral cover indicating temporally stable high latitude reef communities.…”
mentioning
confidence: 99%